2015
DOI: 10.1108/compel-08-2014-0217
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic and thermal parameter identification method for best prediction of temperature distribution on transformer tank covers

Abstract: Purpose -The purpose of this paper is to describe a parameter identification method based on multiobjective (MO) deterministic and non-deterministic optimization algorithms to compute the temperature distribution on transformer tank covers. Design/methodology/approach -The strategy for implementing the parameter identification process consists of three main steps. The first step is to define the most appropriate objective function and the identification problem is solved for the chosen parameters using single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Analytical and numerical models can be employed for the design of the transformer taking into account the well-known advantages of each one: analytic models provide accuracy, less calculation time and simplicity once the model has been developed, whereas numeric models allow one to solve complex geometries and deal with nonlinear materials. Several research works, analyzing the magnetic field distribution and the eddy current power losses in the bushing transformer region, using either numerical or analytical models, have been carried out previously [1,[4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical and numerical models can be employed for the design of the transformer taking into account the well-known advantages of each one: analytic models provide accuracy, less calculation time and simplicity once the model has been developed, whereas numeric models allow one to solve complex geometries and deal with nonlinear materials. Several research works, analyzing the magnetic field distribution and the eddy current power losses in the bushing transformer region, using either numerical or analytical models, have been carried out previously [1,[4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It was also concluded that using non-magnetic inserts reduce power losses in the tank. In [9,11] the temperature distribution on transformer covers is considered. The stray losses in the tank were analytically calculated using Turowski's formula [4].…”
Section: Introductionmentioning
confidence: 99%